Paying Homage to Microvessel Remodeling and Small Vessel Disease in Neurodegeneration: Implications for the Development of Late-Onset Alzheimer’s Disease - Melvin R. Hayden (Journal of Vascular Diseases)
The microvessel neurovascular unit, with its brain endothelial cells (BEC) and blood–brain barrier remodeling, is important in the development of impaired cognition in sporadic or late-onset Alzheimer’s disease (LOAD), which is associated with aging and is highly prevalent in older populations (≥65 years of age). It is also linked with vascular dementia and vascular contributions to cognitive impairment and dementia, including cerebral amyloid angiopathy in neurodegeneration. LOAD is considered to be the number one cause of dementia globally; however, when one considers the role of mixed dementia (MD)—the combination of both the amyloid cascade hypothesis and the vascular hypothesis of LOAD—it becomes apparent that MD is the number one cause. Microvessel BECs are the first cells in the brain to be exposed to peripheral neurotoxins from the systemic circulation and are therefore the brain cells at the highest risk for early and chronic injury. Therefore, these cells are the first to undergo injury, followed by excessive and recurrent wound healing and remodeling processes in aging and other age-related diseases such as cerebrocardiovascular disease, hypertension, type 2 diabetes mellitus, and Parkinson’s disease. This narrative review explores the intricate relationship between microvessel remodeling, cerebral small vessel disease (SVD), and neurodegeneration in LOAD. It also discusses the current understanding of how microvessel dysfunction, disruption, and pathology contribute to the pathogenesis of LOAD and highlights potential avenues for therapeutic intervention.